Genome-wide analysis of the MADS-box gene family of sea buckthorn (Hippophae rhamnoides ssp. sinensis) and their potential role in floral organ development - Zhao, Jing; Xu, Yazhuo; Zhang, Zhihua; Zhao, Meng; Li, Kai; Wang, Fanhong; Sun, Kun (Frontiers in Plant Science, 2024)
Sea buckthorn (Hippophae rhamnoides ssp. sinensis) is a deciduous shrub or small tree in the Elaeagnaceae family. It is dioecious, featuring distinct structures in female and male flowers. The MADS-box gene family plays a crucial role in flower development and differentiation of floral organs in plants. However, systematic information on the MADS-box family in sea buckthorn is currently lacking. In this study, we identified 92 MADS-box genes in the H. rhamnoides ssp. sinensis genome. These genes are distributed across 12 chromosomes and classified into Type I (42 genes) and Type II (50 genes). A variety of cis-acting elements related to development, hormones, and stress were identified in the promoter region. The HrMADS gene were primarily associated with light and phytohormone responses. Based on the FPKM values in the transcriptome data, the expression profiles of HrMADS genes in male and female flowers of sea buckthorn showed that most Type Ⅱ genes had higher expression levels than Type I genes. This suggesting that Type Ⅱ HrMADS may play a more significant role in sea buckthorn flower development. Using the phylogenetic relationship between sea buckthorn and Arabidopsis thaliana, ABCDE model genes of sea buckthorn were identified and correlated. In addition, some ABCDE model-related genes were selected for qRT-PCR analysis in sea buckthorn flowers and floral organs, and the ABCDE model genes may play an important role in the identity determination of sea buckthorn floral organs. This study analyzed the role of MADS-box gene family in the development of flower organs in sea buckthorn, which provides an important theoretical basis for understanding the regulatory mechanism of sex differentiation in sea buckthorn.